Analisis Pengaruh Variabel Makroekonomi Terhadap IHSG Setelah Terjadinya Krisis Subprime Mortgage - Riski Dian Rahmawati; Dinar Melani Hutajulu; Yenny Aulia Rachman (UNIVERSITAS RAHARJA, 2020)
In the 2008 Indonesia returned to the financial crisis driven by the US Subprime Mortgage Crisis. And this has impact on Indonesian economy, so that 2009 was a start of domestic economic recovery. The purpose of this study is to find out the long term significant influence over the inflation variables, the Exchange Rate and BI Rate for IHSG after Subrime Mortgage Crisis in the period during 2009 to 2019 on quarterly payment time. This research is a quantitative research type, with sample of 44 each variable and using ECM method. From the test, it showed that inflation variable has no effect for the Composite Stock Price Index neither at the short-term (0.7372> 0.05) has positive value (0.0117) nor at the Long-term (0.1650> 0.05) has positive value (0.177274), means linear direction for Composite Stock Price Index movement. The Exchange Rate variable was determined neither at short-term Composite Stock Price Index (0.0012 <0.05) has a negative value (-0.7898) means that the exchange rate has opposite direction, nor at the Long-term (0.0000 <0.05) has positive value(1.055191), means linear direction for Composite Stock Price Index movement. BI variable rate did not have an effect for Composite Stock Price Index neither at the short-term (0.1924> 0.05) has negative value (-0.1577) means that the exchange rate has opposite direction, nor at the long-term (0.0025 <0.05) has positive value (-0.821875), means that the exchange rate has opposite direction for Composite Stock Price Index movement.